Peningkatan Layanan Keagamaan di Wilayah Pesisir Kabupaten Lingga Melalui Program Layanan Terapung Keagamaan - Budi, Setia (JURNAL ILMIAH GEMA PERENCANA, 2024)
This article discusses the improvement of religious services in the coastal area of Lingga Regency through a religious floating service program. This program is a service innovation from the Office of the Ministry of Religion of Lingga Regency in providing religious services to coastal communities in Lingga Regency who lack the availability of religious services. This religious floating service program is a form of responsiveness from the Office of the Ministry of Religion of the Lingga Regency to the Integrity Zone Towards a Corruption-Free Area and a Clean Bureaucratic Area and Serving the Indonesian Ministry of Religion program. Where to improve religious services to coastal communities in Lingga District, the Office of the Ministry of Religion of Lingga District has policies such as the Provision of Sea Transportation Facilities in the form of wooden ships, submitting additional budgets to echelon one of the Ministry of Religion and implementing a religious floating service program called Lantera. With the existence of a religious floating service program, a direct interaction is formed between coastal communities who really need religious services and officers who will deliver religious services. Making it easier and save costs for coastal communities